Comparison of salt solution and air drying methods for moisture fixation in highly porous building materials. (October 2017) - Antonov, Yovko Ivanov; Jensen, Rasmus Lund; Møldrup, Per; Pomianowski, Michal
Abstract: In recent years, research has identified some bio-based, porous building materials as good or excellent regulators of moisture in buildings. The ability of a material to absorb, release and store moisture is described by vapour sorption isotherms. It is necessary input to simulations of indoor environmental parameters in regards to human comfort, and nowadays it can be determined by a number of laboratory experiments, each of which characterized by specific specimen size, equilibration time and methodology. The purpose of this study is to experimentally derive isotherms for three bio-based, porous building materials by a standardized testing method, using saturated salt solutions. Furthermore, results from the standard method are compared to values of moisture content for the same materials, obtained by air-drying at different relative humidity. This is done with the aim to compare the findings from the two methods with respect to time and repeatability of the results. Derived isotherms are further used as direct input in the building simulation software BSim, which is capable of predicting indoor environment parameters by solving coupled, transient heat and moisture transport equations using finite volume method discretization. Indoor air relative humidity and moisture content distribution in the construction are compared for the experimented materials and conventional building materials. Results show better agreement between isotherms obtained by standard method and air-drying for low density materials. Simulation results suggest that bio-based, highly porous building materials are comparable to conventional building materials in respect to air relative humidity variations, compared to conventional building materials.